Analysis of the human alpha globin upstream regulatory element (HS-40) in transgenic mice. - Sharpe, J; Chan-Thomas, P; Lida, J; Ayyub, H; Wood, W; Higgs, D (1992)
We have analysed the effect of a 1.4 kb segment of DNA containing the upstream alpha globin regulatory element (HS-40) on human alpha globin gene expression in fetal mice and lines of transgenic mice. High levels of tissue-specific, human alpha mRNA expression were seen in all transgenic animals and in this sense expression was position independent. However, the level of human alpha mRNA expression per integrated gene copy decreased during development and was inversely related to copy number. The limitation in expression with increasing gene copy number was shown to be in cis since homozygotes for the transgene produced twice as much human alpha mRNA as hemizygotes. In many respects HS -40 appears similar to single elements within the previously described beta globin locus control region and in cross breeding experiments we have shown that HS -40 behaves in a similar manner to such elements in transgenic mice.